Effect of adherence to a nutritional bundle protocol on reducing necrotizing enterocolitis in preterm infants - Shahenda Shaaban Ismail; Esraa Ahmed Elmazzahy; Salma Zoheir Elhouchi (Cairo : Shahenda Shaaban Ismail, 2019)
Introduction: NEC is still a major cause of mortality among premature babies, no definitive pathogenesis is defined until now and no specific treatment is available but all what we are trying to do is to avoid its risk factors. Aim: Implementation of nutritional bundle protocol on premature babies (less than 36 weeks PMA) to reduce the incidence of NEC. Methods: A randomized clinical trial enrolled 250 preterm babies in the NICU of Kasr Al-Ainy hospital. They were grouped into "bundle" (120 babies) and "non -bundle" group (130 babies). Bundle group were subjected to nutritional bundle protocol that include: early initiation of enteral feeding, encouraging breast feeding, early advancement of enteral feeding and restriction of antacids use and unnecessary prophylactic antibiotics. Results: Bundle group shows significant decrease in the incidence of NEC (5% versus in the bundle group versus 13% in the non bundle group with p value 0.027). Sepsis incidence also decreased among bundle group (37.5% versus the non bundle group 60% with p value 0.00). Conclusion: Implementation of nutritional bundle protocol proved to be protective against the development of NEC in preterm babies
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Babies; NEC; Nutritional bundle protocol